POPULASI DAN HABITAT KAKATUA HIJAU/BAYAN (Eclectus roratus) DI HUTAN LINDUNG GUNUNG NONA PULAU AMBON - John F. Sahusilawane; Wilma N. Imlabla (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
The green cockatoo (Eclectus roratus) is a species endemic to Maluku whose existence in nature is under pressure due to habitat destruction and human activities. This study aims to determine the population size, distribution patterns, and habitat characteristics of the green cockatoo in the Gunung Nona Protected Forest area of ​​Ambon Island. The study was conducted using field survey methods using point count and line transect techniques. Observations were made at several observation points by recording the number of individuals, vegetation conditions, canopy density, tree height, and distance to water sources. Data were analyzed using population density calculations, multiple linear regression analysis, and ANOVA to determine the relationship between habitat factors and the presence of the green cockatoo. The results showed that the estimated population of the green cockatoo in the Gunung Nona Protected Forest reached an average of 6.9 individuals per hectare with a distribution pattern that tends to cluster in forest areas with dense vegetation and high food source availability. Habitat factors such as tree height, vegetation diversity, canopy density, and proximity to water sources have a significant influence on the presence of this species. Habitat quality is a major factor in supporting the sustainability of the green cockatoo/parrot population in protected forest areas.